The Dissociated Manufacture of the 21st Century Public Administration: in Search of Integration in an Environment of Change - Aguilar, Luis F. (Revista del CLAD Reforma y Democracia, 2019)
This article aims to provide an answer on how to create a public administrative system that ties together the requirement of legitimacy and effectiveness of the government under conditions of scarce resources and in an environment of change. First, an outlook of the last forty years of changes in public administration is provided, which are titled as “the administration of efficiency-effectiveness”, “the administration of legitimacy-legality” and “the administration of interdependencies” (both governmental and social-governmental) and that respectively refer to the New Public Management, the Democratic Transition and the New Public Governance. The causes that drove these three reforms and its essential characteristics are summarized, focusing particularly on the disconnection of the reforms and their effects on public administration. The need for further integration is pointed out as a mean to strengthen the directive effectiveness of the democratic government and to restore social confidence on its competence and efficacy. Regardless of the value of the reforms, the limits of the efficiency-effectiveness and the legitimacy-legality as dissociated approaches are highlighted, as well as its consequences in the functioning of the public administration. Based on the structural interdependence of relations between the actors of contemporary society, including the government, the New PublicGovernance is explained as the steering process of current social and political interactions. Secondly, and according to the New Public Governance principles, a proposal for the integration of the three administrative reforms is offered in order to revaluate the significance and effectiveness of the public administration work.
Keywords: Public Administration Theory; New Public Administration; Governance; Democratization; Open Government; Legitimacy; Effectiveness; Administrative Change